Tuning Isomerism Effect in Organic Bulk Additives Enables Efficient and Stable Perovskite Solar Cells - Qi Zhang; Qiangqiang Zhao; Han Wang; Yiguo Yao; Lei Li; Yulin Wei; Ruida Xu; Chenyang Zhang; Erik O. Shalenov; Yongguang Tu; Kai Wang; Mingjia Xiao (Nano-Micro Letters)
Highlights By anchoring the perovskite sites with the functional groups of CzBP (P = O···Pb, N–H···I and P = O···N–H), the bulk nonradiative recombination is suppressed and ion migration is inhibited. Doping perovskite films with CzBP led to enhanced intercrystallite interactions in the bulk and improved photoluminescence quantum yield. Using a typical electron-rich moiety as the π-linker to replace the classic alkyl spacer in CzBP facilitated the charge-carrier transport processes and the passivation effect of carbazole further contributed to high V OC. The optimized 2,7-CzBP-treated device achieves the highest power conversion efficiency (PCE) of 25.88%, with V OC of 1.189 V for 0.090 cm2 and the perovskite solar cell module with a PCE of 21.04% for 14 cm2. For 2,7-CzBP, the more extended conjugation and the more linear molecular geometry result in a more effective improvement in the performance.